Women and support for terrorism in Pakistan - Fair, C. Christine (Terrorism and political violence, 2018)
While there have been many scholarly inquiries about the sources of support for terrorism among Muslim publics, to date, scholars have generally not asked whether or not gender predicts support for Islamist militancy. Instead, most scholars and officials assume that “men of military age” are the most important segment of interest. Instead, gender is usually treated as a “control variable” rather than a “study variable,” reflecting the paucity of interest in this subject. This is likely an important scholarly and policy-analytic oversight. Many terrorist groups have women’s wings and women-oriented publications and other outreach programs because they understand the important role that mothers, wives, and sisters play in a male family member’s decision to take up arms with a terrorist group. In some conflicts, women also join as combatants. In this paper, we seek to address these scholarly lacunae by examining gender-wise support for two militant groups based in and operating from Pakistan: the Afghan Taliban, which has no female outreach program, and the sectarian Sipha-e-Sahaba-e-Pakistan, which does. We leverage a dataset drawn from a relatively large national survey of Pakistanis collected in 2011 to model support for these groups using gender as an independent variable along with other demographic and control variables. We find that females are significantly more likely to support the sectarian group with a women’s outreach-wing. In contrast, there is no significant gender effect on support for the Afghan Taliban. We argue, from these results, that gender deserves more attention in understanding who supports and participates in Islamist militancy.